2022
DOI: 10.4028/p-ghjg94
|View full text |Cite
|
Sign up to set email alerts
|

Hand Exoskeleton Development Based on Voice Recognition Using Embedded Machine Learning on Raspberry Pi

Abstract: The choice of using speech to control the exoskeleton is based on the number of exoskeletons that are controlled using the EMG signal, where the EMG signal itself has the weakness of the complexity of the signal which is influenced by the position of the electrodes, as well as muscle fatigue. The purpose of this research is to develop an exoskeleton device using voice control based on embedded machine learning on a Raspberry Pi minicomputer. In this study, two feature extraction types namely mel-frequency ceps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A further technique being studied is voice actuation. As an example, an Indonesian group recently reported trials involving a voice-actuated robotic hand, based on ML embedded on a Raspberry Pi minicomputer (Triwiyanto et al , 2022). Two feature extraction techniques and two ML algorithms were evaluated, and trials showed that the mel-frequency cepstral coefficient combined with the k-nearest neighbour ML algorithm gave the most accurate results: 79 ± 14.46% and 90 ± 14.14% for open and close hand commands, respectively.…”
Section: Applications In Exoskeletonsmentioning
confidence: 99%
“…A further technique being studied is voice actuation. As an example, an Indonesian group recently reported trials involving a voice-actuated robotic hand, based on ML embedded on a Raspberry Pi minicomputer (Triwiyanto et al , 2022). Two feature extraction techniques and two ML algorithms were evaluated, and trials showed that the mel-frequency cepstral coefficient combined with the k-nearest neighbour ML algorithm gave the most accurate results: 79 ± 14.46% and 90 ± 14.14% for open and close hand commands, respectively.…”
Section: Applications In Exoskeletonsmentioning
confidence: 99%
“…Incremental learning techniques like online, transfer, and lifelong learning have been utilized to enhance the sEMG-based control system with new knowledge and skills, without the need to retrain the entire model from the beginning [139]. By utilizing techniques that adapt successful models from previous subjects, the training time and effort required to control an upper limb prosthesis can be reduced.…”
mentioning
confidence: 99%
“…By utilizing techniques that adapt successful models from previous subjects, the training time and effort required to control an upper limb prosthesis can be reduced. Additionally, these techniques can allow the user to learn new gestures or movements with the prosthetic hand without interfering with pre-existing ones [138,139].…”
mentioning
confidence: 99%
See 2 more Smart Citations